ANALISIS MANAJEMEN RISIKO TERHADAP KEBERLANGSUNGAN USAHA UMKM DI KOTA BANJARMASIN - Sufi Jikrillah; Muhammad Ziyad; Doni Stiadi (Universitas Lambung Mangkurat, 2021)
The purpose of this research is to identify the risk management process and the sources of risk, to assess the risks that may arise and to analyze the strategies that will be carried out by MSMEs in dealing with or managing these risks in the city of Banjarmasin. This research was conducted in accordance with the risk management process (ISO 31000:2018), namely risk identification, risk analysis, risk evaluation and risk treatment. The population of this research is all MSME business actors in Banjarmasin City. Based on this population, a stratified random sampling method was used for the sampling method of MSME business actors. This is done to reduce the error rate. The use of this sampling method is because the MSMEs that are the research subjects are MSMEs with different types of businesses and occupying different geographical locations. According to Roscoe (1975) quoted by Uma Sekaran (2006). To obtain good results, the number of samples is between 30 and 500. So the number of samples used in this study is 30 SMEs. Home industry products of Tanggui, Crackers and Sasirangan in Banjarmasin City. The results of the identification and risk analysis show that there are 6 main risks faced by MSMEs. The research data are: (1) Capital Risk: (a) lack of capital, and (b) difficulties in accessing capital and capital assistance from banks. (2) HR risk: (a) lack of experts in the production process, (b) lack of training from related parties, and (c) conventional financial management. (3) The risk of raw materials: (a) The price of raw materials continues to rise (expensive), and (b) the durability of raw materials is not long. (4) Process/Operational Risks: (1) limited supply of raw materials, (b) lack of development innovation, and (c) limited expertise in certain production processes. (5) The risk of equipment/machinery: (a) the machine used is not optimal, and (b) the technology used is generally manual.